The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3897/zookeys.1095.72829
|View full text |Cite
|
Sign up to set email alerts
|

Crab spiders (Araneae, Thomisidae) of Jinggang Mountain National Nature Reserve, Jiangxi Province, China

Abstract: A list of 34 thomisid species belonging to 21 genera collected in Jangxi Province of China is provided. Five new species are described: Angaeus xieluae Liu, sp. nov. (♂♀), Lysiteles subspirellus Liu, sp. nov. (♀), Oxytate mucunica Liu, sp. nov. (♀), Pharta lingxiufengica Liu, sp. nov. (♀), Stephanopis xiangzhouica Liu, sp. nov. (♀). A new combination is proposed: Ebelingia forcipata (Song & Zhu, 1993) comb. nov. (ex. Ebrechtella Dahl, 1907). Previously unknown females of E. forcipata (Song & Zh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In China, 311 thomisid species belonging to 52 genera are known ( WSC 2022 ). Although China has the most species- and genus-rich thomisid fauna ( Liu et al 2017 , Li 2020 , Liu et al 2022 , Hong et al 2022 , Zhu et al 2022 ), not much attention has been paid to their systematics in this country. During the past ten years, only a few new species have been discovered from China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China, 311 thomisid species belonging to 52 genera are known ( WSC 2022 ). Although China has the most species- and genus-rich thomisid fauna ( Liu et al 2017 , Li 2020 , Liu et al 2022 , Hong et al 2022 , Zhu et al 2022 ), not much attention has been paid to their systematics in this country. During the past ten years, only a few new species have been discovered from China.…”
Section: Introductionmentioning
confidence: 99%
“…During the past ten years, only a few new species have been discovered from China. Liu et al (2022) identified 34 thomisid species, including five new ones, in the Jinggang Mountain National Nature Reserve in Jiangxi Province ( Liu et al 2022 ), which suggests a high diversity of this group in this region.…”
Section: Introductionmentioning
confidence: 99%
“…Most of pioneer studies on the crab spider of China were carried out by Mingsheng Zhu, and concentrated presented in an indispensable publication: Fauna Sinica: Arachnida : Araneae : Thomisidae ( Song and Zhu 1997 , in Chinese). In the past nearly 20 years, the Chinese Thomisids have been well-studied by Dr. Guo Tang, Dr. Keke Liu, Mr. Yejie Lin and their co-authors etc., along with high quality illustrations and descriptions ( Tang et al 2005 , Tang et al 2006 , Tang et al 2007 , Tang et al 2008a , Tang et al 2008b , Tang et al 2008c , Tang and Li 2009a , Tang and Li 2009b , Tang and Li 2009c , Tang et al 2009 , Tang and Li 2010a , Tang and Li 2010b , Tang et al 2010 , Tang and Li 2012 , Tang et al 2013 , Liu et al 2017 , Lin et al 2019 , Meng et al 2019 , Lin et al 2022 , Liu et al 2022 ). However, there are still many species requiring study ( Liu et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in Jiangxi Province, many spider taxa have been discovered, such as Agelenidae ( Liu et al 2020a , Liu et al 2021 ), Dictynidae ( Liu et al 2018 ), Oonopidae ( Liu et al 2016 , Liu et al 2019 ), Phrurolithidae ( Liu et al 2020b , Liu et al 2020c , Liu et al 2021 , Liu et al 2022d ), Salticidae ( Liu et al 2017b , Liu et al 2022a ), Thomisidae ( Liu et al 2017a , Liu et al 2022c ), Gnaphosidae ( Liu et al 2022b ) and Trachelidae (this study). These discoveries support the fact that this Province is one of the biodiversity hotspots for China.…”
Section: Introductionmentioning
confidence: 99%